PHISHING ATTACKS, AS A FAVOURABLE CONDITION FOR TERRORIST ACTIVITIES - Rusu, Ioana-Raluca (International Journal of Legal and Social Order, 2021)
Since attacks of a phishing type can be included in the category of cybercrime, this paper is aimed at presenting some theoretical aspects specific to this type of criminal offence, the goal being to create logical arguments that would result in conclusions liable to be put to use, but also some methods for counteracting this offence in an incipient stage. These cyber attacks are usually based on a user’s ignorance about the ease with which he is making available, in a virtual environment, his bank account details, credit card details, other personal data, including access passwords. Thus, the money present in the bank accounts, which constitutes the material object of the offence, will be used, without the knowledge of the legal holders, by hackers for banking transactions, which are difficult to follow, in order to finance terrorist activities.